MENINGKATKAN KEMAMPUAN GREEN ECONOMY DALAM MENDORONG PENGEMBANGAN DESA WISATA UNTUK MEWUJUDKAN PEMBANGUNAN YANG BERKELANJUTAN - Mairiza, Khania Taris; Noviarita, Heni (Sekolah Tinggi Ilmu Ekonomi Bakti Bangsa, 2023)
Sustainable development is now the main goal in efforts to achieve community prosperity, maintain environmental sustainability, and promote inclusive economic growth. Green economy, which emphasizes economic growth that does not harm the environment and strengthens social sustainability, is a strategic basis for developing tourist villages. This journal is a review of a selection of journals that are case studies in this review. A literature search was carried out using the Google Scholars online database. The findings of this research are that the researcher concludes, Although many tourist villages have adopted the Green Economy concept as the main basis for their development, the reality presents a series of challenges that need to be overcome. Limited resources, both in terms of finance and infrastructure, are a real obstacle that hinders the ability of tourist villages to fully realize their Green Economy potential. Community resistance to change is also a serious challenge. Increasing understanding of the Green Economy concept also needs to be the main focus in efforts to overcome this obstacle. Educational programs, training and information campaigns can help make people aware of the economic, social and environmental benefits of implementing a Green Economy. Leading to better understanding can reduce resistance and encourage people to play an active role in the sustainability economy. Tourism villages can achieve a more effective and sustainable transformation. Close cooperation between government, society and the private sector is needed to create an environment that supports positive change.